Geometric Quantum Computation with Shortcuts to Adiabaticity (Adv. Quantum Technol. 9/2019). Issue 9 (11th September 2019) - Du, Yanxiong; Liang, Zhentao; Yan, Hui; Zhu, Shiliang
Abstract : Quantum control that is robust against control errors and dephasing process is a key ingredient of quantum computation. In article no.1900013, Yanxiong Du and co‐workers review the recent progresses on the geometric quantum computation with shortcut to adiabaticity. Geometric phase, as acquired in the evolution of Hilbert space, can be used to realize geometric quantum computation that is robust against random noise and systematic errors. Through optimizing the control waveform with shortcut to adiabatic manner, the operation will consolidate the virtues of being fast and robust. Theoretical and experimental results have proven the effectiveness of combining the geometric phase and shortcut to adiabaticity.